Gnade: zu einem Grundbegriff - philosophisch - Splett, Jörg (Zeitschrift für katholische Theologie, 1995)
Mercy is said an "antiquated category" (E. Bloch) due to it's "pathos from above" and it's arbitrariness in privileging only a few elected persons. But on the contrary to exist without being asked for is intolerable. The dignity of the not-asked for is unfounded, if there is not an absolute authority, absolutly free (and therefore liberal, loving) in "calling the non-existent to existence". This call "obliges to goodness, what is better than all goods we can accept" (E. Levinas). And already in that it doesn't cease despite our disobedience, this call becomes forgiving mercy. Most important in this: just the gratuiteness of grace; that is what fills with happiness. (No bliss without gratitude; therefore rights do not found our life and its fulfillment.) The point precisely is the free giving/freely been given. – The same is to be hold concerning the theological problem "nature – grace". Man needs free benevolence. God on that account "must" be free. And man? Should God yield all his gifts to him except just liberty and liberality? Grace and mercy essentially will give (the power to exercise) grace and mercy. God's benediction is answered by the benediction of created man, all the more in the case of the creature raised up in God's inner trinitarian life.